ON THE ROLE OF PEDOMAGNETIC INVESTIGATIONS IN GEOLOGICAL SURVEY OF CRYSTALLINE BASEMENT - BUKOVSKYI, V.; SUKHORADA, A.; KRUHLOV, O.; POPOV, S.; RESHETNYK, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The pedomagnetic investigations made for tectonodomains mapping on crystalline basemant are published.